Indonesian biodiversity spirituality and post COVID-19 ecclesiastical implications - Mojau, Julianus (HTS teologiese studies, 2022)
The enormous impact of the coronavirus disease 2019 (COVID-19) pandemic has caused Indonesian Christian leaders and theologians to become preoccupied with theodicy-humanistic questions rather than considering the rights of life for biodiversity. This is unacceptable because humans are not the only living things with the right to life and are entitled to God’s justice in all-natural disasters. According to biologists and epidemiologists, the pandemic sends a message of ecological injustice. Therefore, by using a method of reading with a perspective of biological diversity, this research argues that humans and other living things have a right to God’s justice amid disasters. The Indonesian spirituality of biological diversity, which is in line with the gratitude of Francis of Assisi and Calvin’s idea of living in a church that considers God’s justice for all creation, can serve as an epistemological foundation for developing theodicy-ecological ecclesiology.Contribution: Considering the spirituality of biodiversity enables churches in Indonesia to embrace biodiversity as fellow creatures of God post-pandemic. In this way, they can affirm their ecclesiastical identity as the ecological body of Christ amid ecological injustice.